Rancang Bangun Sistem Informasi Pemetaan UMKM Menggunakan Metode Extreme Programming - Yoga, I Putu Agus Tirta; Wijaya, I Nyoman Yudi Anggara; Mega Putra, Anak Agung Gede Adi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the economy of developing countries, including Indonesia, especially in creating jobs, reducing poverty, and driving economic growth. In Indonesia, MSMEs contribute more than 95% of total businesses and have proven to be resilient in the face of the 1997–1998 monetary crisis. However, in Susut Village, MSMEs still face various challenges, especially in terms of digitalization and limited infrastructure, which hinder their growth potential. To overcome these problems, this study designs and builds a website-based MSME Mapping Information System equipped with a Geographic Information System (GIS) to present accurate location and type of business information. This system was developed using the Extreme Programming (XP) method which focuses on an iterative and collaborative approach between the development team and users. The purpose of this system is to empower village communities, increase access to MSME information, expand market reach, and introduce superior village products to a wider audience. Thus, it is hoped that this system can encourage local economic growth and improve community welfare.